Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

The effects of phosphorus on the fate and transformation of sediment-associated cadmium from river sediments - Fen Xu; Yuhui Liao; Shihao Bai; Rui Yang; Yaoming Li; Jianfei Yuan (Science of The Total Environment, 2024)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Contribution of Baroreflex Afferent Pathway to NPY-Mediated Regulation of Blood Pressure in Rats - Yang Liu; Shu-Yang Zhao; Yan Feng; Jie Sun; Xiao-Long Lu; Qiu-Xin Yan; Ying Li; Zhuo Liu; Lu-Qi Wang; Xun Sun; Shijun Li; Guo-Fen Qiao; et al. (Neuroscience Bulletin, 2020)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Glycyrrhizic acid activates chicken macrophages and enhances their Salmonella-killing capacity in vitro - Bai-kui Wang; Yu-long Mao; Li Gong; Xin Xu; Shou-qun Jiang; Yi-bing Wang; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2018)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Isolation and Characterization of the Cold-Induced Phyllostachys edulis AP2/ERF Family Transcription Factor, peDREB1 - Lei Liu; Xiao-Lu Cao; Rui Bai; Na Yao; Lu-Bin Li; Cong-Fen He (Plant Molecular Biology Reporter, 2012)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

Dynamics of sandy desertification and its driving forces in western Jilin Province - Fang Li; Yan-fen He; Zhi-ming Liu; Bai Zhang (Chinese Geographical Science, 2004)